Is the Collective Model of Labor Supply Useful for Tax Policy Analysis? : A Simulation Exercise - Olivier Bargain; Nicolas Moreau (Institute for the Study of Labor (IZA), 2005)
The literature on household behavior contains hardly any empirical research on the withinhousehold distributional effect of tax-benefit policies. We simulate this effect in the framework of a collective model of labor supply when shifting from a joint to an individual taxation system in France. We show that the net-of-tax relative earning potential of the wife is a significant determinant of intrahousehold negotiation but with very low elasticity. Consequently, the labor supply responses to the reform are entirely driven by the traditional substitution and income effects as in a unitary model. For some households only, the reform alters the intrahousehold distribution in a way that tends to change normative conclusions. A sensitivity analysis shows that the collective model would be required if the tax reform was both radical and of extended scope.
Keywords: H31; D12; J22; D11; C71; 330; collective model; intrahousehold allocation; household labor supply; tax reform; Arbeitsangebot; Haushaltsökonomik; Familienökonomik; Steuer; Steuerreform; Wirtschaftspolitische Wirkungsanalyse; Theorie; Frankreich